Tax Awareness, Tax Knowledge, and Tax Sanctions on Motor Vehicle Taxpayer Compliance - Daru Ramadhan; Haninun Haninun (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
Motor vehicle tax compliance remains an important concern despite the rising capacity of local governments to generate revenue from this sector. The persistence of low compliance is closely related to behavioral factors and insufficient taxpayer understanding. This study focuses on examining how tax awareness, taxpayer knowledge, and. Tax the level of compliance among motor vehicle taxpayers at the SAMSAT Office of Bandar Lampung City. The research adopts a quantitative design using primary data gathered from 100 motor vehicle owners through questionnaires. To examine how different factors relate to one another, multiple linear regression was employed. The results demonstrate that tax awareness, taxpayer knowledge, and tax sanctions each have a significant positive effect on taxpayer compliance. These findings highlight that compliance is influenced by a combination of internal and external factors. Accordingly, strengthening tax-related education and maintaining consistent implementation of tax sanctions are essential strategies to encourage voluntary compliance.